Cyclodextrin encapsulated catechin: Effect of pH, relative humidity and various food models on antioxidant stability. (November 2017) - Ho, Siyin; Thoo, Yin Yin; Young, David James; Siow, Lee Fong
Abstract: The antioxidant catechin is astringent in taste, sparingly soluble in water and sensitive to oxygen, light and pH. These properties can restrict its application in food products. The present study investigated the effect of pH, relative humidity (RH) and various food components on this polyphenol's antioxidant stability, before and after encapsulation by β− cyclodextrin (β−CD) and by some alkylated β−CD derivatives. Catechin was observed to be very sensitive to pH (alkaline) and high relative humidity (>65%) but there was relatively little loss of antioxidant activity (61% antioxidant retention) for cyclodextrin inclusion complexes (ICs) under these conditions. Interestingly, free catechin degraded dramatically in a 40% protein model compared to a sugar or oil model, but this degradation was significantly retarded by β-CD complexation. These results suggest that protection of antioxidants and other sensitive components by β-CD encapsulation may have applications in functional foods and health supplements. Highlights: Catechin is sensitive to alkaline pH and high RH but inclusion complex is not. Encapsulation of CAT with β-CD provides protection. CAT-HPβ-CD, CAT-Mβ-CD were collapsed but CAT-β-CD remained good condition at high %RH. Catechin degraded dramatically from its initial amount in a protein model. Catechin stability was improved in protein model by β-CD encapsulation.